PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT. PERKEBUNAN NUSANTARA II (TANJUNG MORAWA MEDAN) PRODUKSI KELAPA SAWIT - Debby Fransiska Gultom; Widya Wati; Junita Sinaga; Della Ananda Putri (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2019)
Competence is something that is inherent in a person that can be measured by certain measuring instruments. Competence is very helpful in improving employee performance. In addition to competence, training is an environmental forum for employees, where they obtain or study specific attitudes, abilities, expertise, knowledge and behaviors related to work. The training is useful for identifying and assessing performance through planned learning to improve employee performance in the company. The purpose of this study was to determine the effect of competence and training on employee performance at PT. Perkebunan Nusantara II (Tanjung Morawa Medan) for palm oil production. The method of analysis using multiple linear regression study. The population of the study was 130 employees with a sample of 98 respondents. Based on the data analysis, competence and training have a significant effect on performance.